Having co-morbid cardiovascular disease at time of cancer diagnosis: already one step behind when it comes to HRQoL?. (2nd December 2019) - Schoormans, Dounya; Husson, Olga; Oerlemans, Simone; Ezendam, Nicole; Mols, Floortje
Abstract: Background: The relation between cardiovascular disease (CVD) present at the time of cancer diagnosis and Health-Related Quality of Life (HRQoL) assessed years after cancer diagnosis has – to our knowledge – not been studied. The objective is, therefore, to examine the relation between co-morbid CVD at cancer diagnosis and HRQoL among cancer survivors diagnosed with colorectal, thyroid, prostate, endometrium, ovarian cancer, melanoma, (non-)Hodgkin lymphoma, chronic lymphocytic leukemia (CLL), or multiple myeloma (MM) in an exploratory population-based cross-sectional study. Material and methods: Analyses were performed on combined data sets from the PROFILES and Netherlands Cancer Registry (NCR). Data on co-morbid CVD at cancer diagnosis was extracted from the NCR. HRQoL was measured via PROFILES at a median of 4.6 years after cancer diagnosis. General Linear Model Analyses were run for the total group of cancer survivors and for each malignancy. Results: In total, 5930 cancer survivors (2281 colorectal, 280 thyroid, 1054 prostate, 177 endometrium, 389 ovarian cancer, 212 melanoma, 874 non-Hodgkin and 194 Hodgkin lymphoma, 242 CLL, and 227 MM survivors) were included. For the total group, survivors who had a CVD at cancer diagnosis ( n  = 1441, 23.4%) reported statistically significant and clinically important lower scores on global QoL and physical functioning and higher scores for dyspnea ( p  < .05) compared to those without CVD. Co-morbid CVD at cancer diagnosis was negatively related to global QoL, the five functional scales and the symptoms fatigue and dyspnea across most malignancies (i.e., colorectal, and prostate cancer, non-Hodgkin lymphoma, ovarium cancer, melanoma, and CLL). No significant relations were found among thyroid and endometrium cancer, Hodgkin lymphoma and MM survivors, likely due to small numbers. Conclusion: In conclusion, co-morbid CVD at cancer diagnosis was negatively related to HRQoL, especially to global QoL, physical and role functioning, and the symptoms fatigue and dyspnea.